2007
DOI: 10.1186/1742-2094-4-21
|View full text |Cite
|
Sign up to set email alerts
|

A novel p38α MAPK inhibitor suppresses brain proinflammatory cytokine up-regulation and attenuates synaptic dysfunction and behavioral deficits in an Alzheimer's disease mouse model

Abstract: Background: An accumulating body of evidence is consistent with the hypothesis that excessive or prolonged increases in proinflammatory cytokine production by activated glia is a contributor to the progression of pathophysiology that is causally linked to synaptic dysfunction and hippocampal behavior deficits in neurodegenerative diseases such as Alzheimer's disease (AD). This raises the opportunity for the development of new classes of potentially disease-modifying therapeutics. A logical candidate CNS target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 81 publications
7
183
0
Order By: Relevance
“…Finally, given that the inhibition of p38 activation is sufficient to prevent Aβ-induced neurotoxicity, as also observed by others [33,56] , atorvastatin treatment controls AβO-induced neurotoxicity through the regulation of p38MAPK phosphorylation. Activated p38MAPK is observed in human AD brain tissue [57] and in AD-relevant animal models [58,59] , and cell culture studies strongly implicate p38MAPK in the increased production of proinflammatory cytokines in the glia activated by Aβ [60] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, given that the inhibition of p38 activation is sufficient to prevent Aβ-induced neurotoxicity, as also observed by others [33,56] , atorvastatin treatment controls AβO-induced neurotoxicity through the regulation of p38MAPK phosphorylation. Activated p38MAPK is observed in human AD brain tissue [57] and in AD-relevant animal models [58,59] , and cell culture studies strongly implicate p38MAPK in the increased production of proinflammatory cytokines in the glia activated by Aβ [60] .…”
Section: Discussionmentioning
confidence: 92%
“…Signaling pathways involved in the neuroprotection afforded by atorvastatin against AβO-induced synaptotoxicity Based on the fact that the activation of p38MAPK plays an important role in the intracellular mechanisms of neurodegeneration, in particular Aβ 1-42 -induced neurotoxicity [33,34] , we investigated whether p38MAPK is involved in the neuroprotective effects afforded by atorvastatin. The results showed that an icv injection of AβOs led to a significant increase in phospho-p38MAPK protein expression without a concurrent increase in the total level of this kinase.…”
Section: Identification Of Aβ Peptide Solutions and The Accumulation mentioning
confidence: 99%
“…Previous studies demonstrating the effects of p38 MAPK in hippocampal slices or APP-transgenic mice used p38 MAPK inhibitors, which cannot distinguish neuronal p38 MAPK effects and microglial p38 MAPK effects (22,25). In attempting to dissect the role of p38 MAPK in AD, it is essential to distin- …”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…p38␣ MAPK mediates A␤-initiated microglial inflammatory activation (21, 22), phosphorylates Tau protein in neurons (20,23,24), and mediates A␤-induced synaptic impairment in the cultured hippocampal slice (25). However, no experiments have yet elucidated whether p38 MAPK phosphorylates BACE1 and regulates A␤ generation.Previous studies demonstrating the effects of p38 MAPK in hippocampal slices or APP-transgenic mice used p38 MAPK inhibitors, which cannot distinguish neuronal p38 MAPK effects and microglial p38 MAPK effects (22,25). In attempting to dissect the role of p38 MAPK in AD, it is essential to distin- …”
mentioning
confidence: 99%
“…For example, inhibitors for TLR7 and TLR9 have been studied for the treatment of autoimmune diseases (54), and the TLR4 antagonist, eritoran tetrasodium (E5564), is under clinical trial for the treatment of septic shock patients (55). Potential immunomodulators also include inhibitors of TLR signaling molecules, such as p38␣ MAPK (56,57), MK2 (58), or IRAK4 (59 -61). As a strong inhibitor of cytokine production, usage of DFK1012 or related molecules may have some advantages over treatment with Infliximab, an anti-TNF-␣ antibody, or other related antiinflammatory drugs targeting inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%